Pengaruh Kompetensi Dosen Tamu Mata Kuliah PPh OP Terhadap Kepuasan Mahasiswa - N. Purnomolastu; D. Tialurra Della Nabila (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2014)
One of the most critical objectives in all institutions of higher learning is attaining student satisfaction because student satisfaction has become an increasingly important component of institutional reports as a means of accountability to educational stakeholders. The aims of this study is to determine the influence of guest lecturer competence of PPh OP toward students’ satisfaction at Prodi Perpajakan Politeknik Ubaya. The finding shows that the competence of guest lecturer is significantly relates to student satisfaction positively.